A Product Hybrid GMRES Algorithm for Nonsymmetric Linear Systems (Journal of Computational Mathematics, 2018)
It has been observed that the residual polynomials resulted from successive restarting cycles of GMRES($m$) may differ from one another meaningfully. In this paper, it is further shown that the polynomials can complement one another harmoniously in reducing the iterative residual. This characterization of GMRES($m$) is exploited to formulate an efficient hybrid iterative scheme, which can be widely applied to existing hybrid algorithms for solving large nonsymmetric systems of linear equations. In particular, a variant of the hybrid GMRES algorithm of Nachtigal, Reichel and Trefethen (1992) is presented. It is described how the new algorithm may offer significant performance improvements over the original one.